PENGARUH PROFITABILITAS, FIRM SIZE DAN GOOD CORPORATE GOVERNANCE UNTUK MENGUJI MANAJEMEN LABA - Gendro Wiyono; Agus Dwi Cahya; Sheli Marselina Br PA (JURNAL ILMIAH EDUNOMIKA, 2021)
This study was conducted with aim of analyzing the affect of Profitability, Firm Size, Independent Board of Commissioners and Audit Committee used to test earning management. The oil and gas sub-sector company listed on the Indonesia Stock Exchange for the period 2015-2019 were the population of this study. The method used is purposive sampling. The Sample of study used by 8 companies. This type of research is quantitative with secondary data sources. The analytical technique used is multiple linear regression analysis. Data processed on SPSS program version 23.0. The results of this study showed that profitability has a significant positive effect on earning management in oil and gas sub-sector companies. Firm size has a significant positive effect on earning management in oil and gas sub-sector companies. The independent board of commissioners has no significant impact on earning management in oil and gas sub-sector companies. The audit committee has no effect on earning management in oil and gas sub-sector companies. Keywords: profitability, firm size, good corporate governance, and earning management.